Endoscopic Ultrasound-Guided Ablation of Focal Pancreatic Lesions: The GRUPUGE Perspective - Bispo, Miguel (2020)
Focal pancreatic lesions include a heterogeneous group of solid and cystic lesions, with different natures and variable clinical, imagiological, and pathological characteristics. Several endoscopic ultrasound (EUS)-guided ablative techniques have been tested during the last decade for the treatment of these pancreatic lesions, mostly consisting of the injection of ablative agents and, more recently, radiofrequency ablation. The most encouraging EUS-guided ablation outcomes are being reached in the treatment of some pancreatic cystic neoplasms and small (≤2 cm) pancreatic neuroendocrine tumours (pNETs). Data supporting a potential role of ablative therapies in the treatment of pancreatic ductal adenocarcinoma is still lacking. In this article, GRUPUGE presents an updated perspective of the potential role of EUS-guided ablation for the treatment of pancreatic cystic neoplasms and pNETs, addressing the selection criteria and technical issues of different techniques and analysing recent data on their safety and efficacy.